Faraway, so close: the impact of the Russia-Ukraine war on political violence in Asian countries - Michele Di Maio; Patricia Justino; Valerio Leone Sciabolazza; Cecilia Nardi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
We show that the Russia-Ukraine-war-induced changes in the international price of wheat affected political violence in Asia. Using data from 13 countries and more than four million cell-level observations, we show that a higher wheat price increases political violence in areas that are more suitable to produce that crop. We interpret this evidence as consistent with a rapacity effect being at play: the higher value of agricultural output increases the incentive to violently appropriate it. Our result is robust to a number of falsification and robustness tests. The effect is heterogeneous across countries and cell types: in line with our interpretation of the empirical findings, the effect is larger in countries that are net exporters of wheat and in cells that are rural. We also show that a higher price of wheat increases political violence more in countries that are low-income, fragile, and characterized by the presence of anti-government or terrorist groups, indicating that a higher value of crop production is more likely to fuel violence in areas that are poor or not politically stable.
Keywords: F13; F14; Q17; Q54; 330; Russia-Ukraine war; commodity prices; agricultural trade; agricultural suitability; rapacity effect